Illegal subdivisions in Spain: expansion and effects of irregular urban planning in the regulated city environment - López Casado, David; Mulero Mendigorri, Alfonso (Anales de Geografía de la Universidad Complutense, 2022)
The phenomenon of illegal allotment, as it is understood in this research, had its stage of special incidence in Spain between the seventies and the first nineties, remaining active until today. Although it was slowed down and, in certain cases, redirected, the footprint of these processes developed outside of planning still continues to affect the territorial structures where they are located. Starting from the conceptualization of the phenomenon, an update is made of it based on its evolution in four regions of the country, analyzing the works prepared for its quantification and characterization, as well as the response that regional administrations have given to address its control. The main conclusions suggest that the persistence of the phenomenon is leading to growing social conflict as well as significant territorial and environmental impacts.
Keywords: Illegal allotment; urban sprawl; environmental impact; territorial impact; social conflict